Induction of EnR stress by Melatonin enhances the cytotoxic effect of Lapatinib in HER2-positive breast cancer. (10th October 2021) - Sang, Xiaolin; Li, Li; Rui, Chunhua; Liu, Yichao; Liu, Zundong; Tao, Zhiwei; Cheng, Hailing; Liu, Pixu
Abstract: Despite HER2-targeted cancer treatments have provided considerable clinical benefits, resistance to HER2-targeted agents will inevitably develop. Targeting non-oncogene vulnerabilities including endoplasmic reticulum (EnR) stress has emerged as an attractive alternative approach to improve the efficacy of existing targeted cancer therapies. In the current study, we find that Melatonin sensitizes HER2-positive breast cancer cells to the dual tyrosine kinase inhibitor Lapatinib in vitro . Mechanistically, Melatonin enhances the cytotoxic effects of Lapatinib through promoting excessive EnR stress-induced unfolded protein response (UPR) and ROS overaccumulation. Consistently, the antioxidant N-acetylcysteine remarkably reverses the effects of the drug combination on ROS production, DNA damage and cytotoxicity. Furthermore, Melatonin significantly enhances the anti-tumor effect of Lapatinib in an HCC1954 xenograft model. Meanwhile, Lapatinib resistant HER2-positive breast cancer cells (LapR) display lower basal expression levels of UPR genes and enhanced tolerance to EnR stress with attenuated response to Brefeldin A and Tunicamycin. Importantly, Melatonin also increases the sensitivity of HCC1954 LapR cells to Lapatinib. Together, our findings highlight the potential utility of Melatonin as an adjuvant in the treatment of primary or therapy resistant HER2-positive breast cancer via EnR stress-mediated mechanisms. Highlights: Melatonin sensitizes HER2+ breast cancer cells to Lapatinib in vitro and in vivo . The cytotoxic effect of Melatonin and Lapatinib arises from excessive UPR and ROS. Lapatinib resistant HER2+ breast cancer cells exhibit enhanced EnR-stress tolerance. The drug combination is effective in Lapatinib resistant HER2+ breast cancer cells.